Representativeness in contemporary British drama: a critical discourse analysis in Jonathan Harvey’s Beautiful Thing - Pinto, Josane Daniela Freitas; Oliveira, Wellington Ruan Correa (REVELL - REVISTA DE ESTUDOS LITERÁRIOS DA UEMS, 2018)
This research aims to analyze the contemporary British drama from the Critical Discourse Analysis (CDA) in the play Beautiful Thing, trying to describe how the characters construct their identities along the text to establish the aspect of representativeness in the play. The methodology used was the theoretical discussion and the analysis with data from the play. It is divided into three sections; the first is a historical overview on 1990s British drama, presenting facts and changes. The second is a discussion on the theoretical background about CDA, conceptualized mainly by van Dijk (2001) and Fairclough (1992; 2003); and Identities with Castells (2010), Buckingham (2008), Hall (1997), and Verluys (2007). Afterwards, the play is analyzed from these concepts, where the linguistic instruments in the characters’ discourses, responsible for the construction of their identities, are searched in the play and exemplified with fragments.